Projection-iterative version of the method of local variations for the problems of local stability of spherical shells - Hudramovich, V. S.; Hart, E. L. (Reports of the National Academy of Sciences of Ukraine, 2015)
A projection-iterative scheme of a realization of the method of local variations for solving the variational problems with quadratic functional is proposed and theoretically grounded. By the example of solving the problem of local stability of a spherical shell, the practical efficiency of the proposed modification of the method of local variations is demonstrated.